2013
DOI: 10.1038/cddis.2013.104
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermia enhances mapatumumab-induced apoptotic death through ubiquitin-mediated degradation of cellular FLIP(long) in human colon cancer cells

Abstract: Colorectal cancer is the third leading cause of cancer-related mortality in the world; the main cause of death of colorectal cancer is hepatic metastases, which can be treated with hyperthermia using isolated hepatic perfusion (IHP). In this study, we report that mild hyperthermia potently reduced cellular FLIP(long), (c-FLIPL), a major regulator of the death receptor (DR) pathway of apoptosis, thereby enhancing humanized anti-DR4 antibody mapatumumab (Mapa)-mediated mitochondria-independent apoptosis. We obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 46 publications
(54 reference statements)
2
22
0
1
Order By: Relevance
“…We observed that no restoration of c-FLIPL occurred during treatment with SP6001125. This observation was consistent with other researchers’ reports [27,28]. …”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…We observed that no restoration of c-FLIPL occurred during treatment with SP6001125. This observation was consistent with other researchers’ reports [27,28]. …”
Section: Resultssupporting
confidence: 94%
“…We observed in Figure 5C that 25% of protein synthesis was inhibited in hyperthermia, whereas there was 46% protein synthesis inhibition in oxaliplatin combined with hyperthermia. Figure 5D shows that reduction of c-FLIP L level by 42°C for 1 h heating alone was more than that by 30 µg of cyclohexmide which inhibits protein synthesis by 99% [28]. These results suggest that protein synthesis inhibition alone is not a major factor for downregulation of FLIP L by hyperthermia.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies presented that many proteins including survivin and c-FLIP are degraded through activation of ubiquitination [45][46][47]. To confirm the effect of ubiquitination on degradation of survivin and c-FLIP expression, we analyzed ubiquitination of survivin and c-FLIP by honokiol.…”
Section: Honokiol Induces Survivin and C-flip Degradation Through Actmentioning
confidence: 99%
“…Although the preclinical/clinical studies demonstrated the safety and activity of TRAIL, its short elimination half-life (approximately 30 min) is a main obstacle (3, 4). To overcome this obstacle, researchers have devised several strategies, including using humanized anti-TRAIL receptor antibodies (58) and a chimeric human TRAIL/human IgG-Fc fusion protein (9). In this study, we attempted to develop secretory TRAIL-natural killer (NK) cell-based therapy.…”
Section: Introductionmentioning
confidence: 99%